"Grass auseinandergeschrieben:" Günter Grass's Hundejahre and Mimesis. (5th February 2013) - Minden, Michael
<x xml:space="preserve">Abstract</x> The aim of this article is to contribute to an assessment of Grass's achievement as an artist in the condition of post‐war German democratic capitalism. Using the concept of Mimesis as it is developed by Adorno and Horkheimer in the Dialektik der Aufklärung, the article offers an analysis of Grass's neglected masterpiece Hundejahre, and attempts particularly to explain the peculiar and perplexing motif of scarecrows at its center. The results of this reading suggest how Grass found an aesthetically adequate response to the Holocaust for one shamed by it. At the same time, he fought on a second front, in defense of the literary imagination against the effects of celebrity in the media. In finding means to set free the energies of Mimesis, Grass of necessity engaged with those of Ratio too, and produced a text which taps the wellsprings of creativity without falling victim to either irrationalism or complacency.